2020
DOI: 10.37765/ajmc.2020.88515
|View full text |Cite
|
Sign up to set email alerts
|

Updates in treatment of adults with chronic cough

Abstract: Chronic cough is the most common symptom for which individuals seek medical advice. This health issue has a substantial impact on a person's quality of life and can produce complications such as vomiting, fractures, muscle pain, syncope, and depression. Pharmacists and managed care professionals should recognize the complicated etiology of chronic cough and its difficult management. As there are currently no available therapies specifically indicated for this, the emerging treatment options that are targeted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The diagnosis of OUD is based on the guidelines presented in the Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) [ 5 , 6 ], in which it has been reported that OUD is defined as a “problematic pattern of opioid use leading to clinically significant impairment or distress” [ 2 ]. Opioid medications are employed for the treatment of moderate-to-severe chronic cancer and non-cancer pain [ 7 , 8 , 9 , 10 , 11 , 12 ], although some opioids can be used for treating diarrhea [ 13 , 14 , 15 ] and cough [ 16 , 17 ]. Moreover, opioids can be used by patients suffering from chronic backaches [ 18 , 19 ] and headaches [ 20 , 21 ], by people recovering from surgery [ 22 , 23 , 24 ], and by both adults and children who have suffered serious injuries in falls, while playing sports, or in auto accidents, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of OUD is based on the guidelines presented in the Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) [ 5 , 6 ], in which it has been reported that OUD is defined as a “problematic pattern of opioid use leading to clinically significant impairment or distress” [ 2 ]. Opioid medications are employed for the treatment of moderate-to-severe chronic cancer and non-cancer pain [ 7 , 8 , 9 , 10 , 11 , 12 ], although some opioids can be used for treating diarrhea [ 13 , 14 , 15 ] and cough [ 16 , 17 ]. Moreover, opioids can be used by patients suffering from chronic backaches [ 18 , 19 ] and headaches [ 20 , 21 ], by people recovering from surgery [ 22 , 23 , 24 ], and by both adults and children who have suffered serious injuries in falls, while playing sports, or in auto accidents, etc.…”
Section: Introductionmentioning
confidence: 99%